Method for Indirect Quantification of CH4 Production via H2O Production Using Hydrogenotrophic Methanogens - Taubner, Ruth-Sophie; Rittmann, Simon K.-M. R. (Frontiers in Microbiology, 2016)
ydrogenotrophic methanogens are an intriguing group of microorganisms from the domain Archaea. They exhibit extraordinary ecological, biochemical, physiological characteristics \colorbox{yellow}{and have a huge biotechnological potential}. Yet, the only possibility to assess the methane (CH$_4$) production potential of hydrogenotrophic methanogens is to apply gas chromatographic quantification of CH$_4$. In order to be able to effectively screen pure cultures of hydrogenotrophic methanogens regarding their CH$_4$ production potential we developed a novel method for indirect quantification of \colorbox{yellow}{the} volumetric CH$_4$ production rate by measuring \colorbox{yellow}{the} volumetric water production rate. This \colorbox{yellow}{ } method was established in serum bottles for cultivation of methanogens in closed batch cultivation mode. Water production was \colorbox{yellow}{estimated} by determining the difference in mass increase in an isobaric setting. This novel CH$_4$ quantification method is an accurate and precise analytical technique, \colorbox{yellow}{which can be used} to rapidly screen pure cultures of methanogens regarding \colorbox{yellow}{their} volumetric CH$_{4}$ evolution rate. \colorbox{yellow}{It} is a cost effective alternative \colorbox{yellow}{determining} CH$_4$ production of methanogens over CH$_4$ quantification by using gas chromatography, especially if \colorbox{yellow}{ } applied as a high throughput quantification method. \colorbox{yellow}{Eventually, the} method can be universally applied for quantification of CH$_4$ production from psychrophilic, thermophilic and hyperthermophilic hydrogenotrophic methanogens.